2021
DOI: 10.1242/jeb.242172
|View full text |Cite
|
Sign up to set email alerts
|

Age-related reductions in the number of serial sarcomeres contribute to shorter fascicle lengths but not elevated passive tension

Abstract: We investigated age-related changes to fascicle length, sarcomere length and serial sarcomere number (SSN), and how this affects passive force. Following mechanical testing to determine passive force, the medial gastrocnemius muscle of young (n=9) and old (n=8) Fisher 344BN hybrid rats was chemically fixed at the optimal muscle length for force production; individual fascicles were dissected for length measurement, and laser diffraction was used to assess sarcomere length. Old rats had ∼14% shorter fascicle le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 44 publications
9
12
0
Order By: Relevance
“…The SSN, SL, and FL values (Figures 3-5) we observed for the rat soleus, LG, and MG are consistent with previous studies (10,18,49,5860). In line with previous reports from Power et al (10), we observed 14% fewer serial sarcomeres in the MG of old compared to young rats, with 14% shorter fascicles and no significant difference in SL at a 90° ankle angle. We can now expand this age-related reduction in SSN to the rat soleus and LG.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The SSN, SL, and FL values (Figures 3-5) we observed for the rat soleus, LG, and MG are consistent with previous studies (10,18,49,5860). In line with previous reports from Power et al (10), we observed 14% fewer serial sarcomeres in the MG of old compared to young rats, with 14% shorter fascicles and no significant difference in SL at a 90° ankle angle. We can now expand this age-related reduction in SSN to the rat soleus and LG.…”
Section: Discussionsupporting
confidence: 93%
“…The stiffer extracellular matrix (ECM) in older individuals (40,41) may also limit the mechanical stimuli imposed on muscle contractile tissue, as pre-training collagen content and packing density are negatively associated with hypertrophic outcomes (42,43). As well, if aged muscle has a lower SSN to begin with (10), they may incur greater stretch and thus damage than young muscle for a given magnitude of joint rotation, leading to a longer recovery period (36,44,45). There has, however, been no direct investigation into whether older individuals can add sarcomeres in series to the same extent as young following long-term eccentric training.…”
Section: Introductionmentioning
confidence: 99%
“…Immobilizing the rat ankle in full dorsiflexion for 2 weeks to position the plantar flexor muscles in a lengthened position, the present study investigated whether ultrasound-derived FL measurements TA B L E 5 Relationships between percentage change in ultrasound-derived fascicle length (FL) from pre to post-cast and percentage change in serial sarcomere number of dissected fascicles from the un-casted to casted leg (n = 15 rats). Our values for muscle wet weight, SSN, SL, FL and ultrasoundderived PA are within previously reported ranges for the rat soleus (Booth, 1977;Chen et al, 2020;Hinks, Jacob et al, 2022;Mele et al, 2016;Peixinho et al, 2011;Soares et al, 2007) and gastrocnemii (Booth, 1977;Mele et al, 2016;Ochi et al, 2007;Peixinho et al, 2011;Power et al, 2021;Woittiez et al, 1986).…”
Section: Discussionsupporting
confidence: 90%
“…Such interaction effects could include, for example, an increase of passive stiffness in relative rather than absolute terms, which has been suggested based on the observation that active contractions become weaker with age while passive muscle properties remain unchanged [ 56 ]. Moreover, the increase in passive force could occur with, and be partially caused by, age-related reduction in optimal muscle lengths [ 29 ]. Tendons, which affect force transmission and a muscle’s length and velocity trajectory during movements, may also undergo age-related structural changes [ 57 ], although the changes in tendon stiffness can be insignificant in the upper limbs [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Roughly fitting an exponential function to the passive tension data for muscle fibre bundles from mice [ 14 ] and humans [ 15 ] suggests an increase in the range of 0–30% in r p . Changes in the optimal muscle length also affect r p , so that, for example, the 14% reduction observed in older mice [ 29 ] translates to a reduction of approximately 12% in r p . We chose r p = 5 based on Winters [ 26 ] as the lower parameter value and a relatively high 60% increase to r p = 8 to balance out the overall low values compared to those used by Thelen [ 20 ] to simulate the effects of ageing on ankle function ( r p ≈ 8 for young and r p = 10 for old muscles).…”
Section: Methodsmentioning
confidence: 99%